Integrasi Al-Tarbiyah Bil-Qudwah dalam Kerangka Prophetic Education QS.Al-Ahzab Ayat 21: Relevansi dan Tantanganya di Era Digital - M. Nuzulul Ulum; Tulus Musthofa; Amri Saputra; Rosnani Hashim (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
This study aims to analyze the integration of al-Tarbiyah bil-Qudwah within the framework of Prophetic Education based on Qur'an Surah Al-Ahzab verse 21, focusing on its relevance and challenges in the digital era. Although research on role modeling and prophetic education has progressed, studies that systematically integrate both within the context of digital transformation remain limited, leaving a conceptual gap in developing adaptive Islamic education models. This research employs a qualitative library-based approach by examining classical and contemporary literature to construct the theoretical relationship between role modeling, prophetic values humanization, liberation, and transcendence and modern educational practices. The findings indicate that role modeling remains an effective strategy for instilling moral and spiritual values; however, it requires contextual adaptation through the consistency of educators’ behavior in both physical and digital spaces, the strengthening of institutional cultures grounded in uswah hasanah, and the development of digital ethics evaluation indicators. The theoretical contribution of this study lies in formulating an integrative conceptual framework that bridges normative foundations with contemporary pedagogical needs, thereby expanding the discourse on Prophetic Education toward a more contextual and operational direction. Therefore, this study recommends empirical testing of the proposed framework as well as the development of a measurable and replicable digital qudwah implementation model across various educational levels.